Fishermen, fishmongers, and the sea economic restructuring and gender dynamics in a Philippine community - Turgo, Nelson Nava (Philippine studies : historical and ethnographic viewpoints, 2015)
"This article provides a place-and work-specific exposition of gendered transformation in a local economy in Quezon province in the Philippines, where the declining productivity of fisheries since 1985 has seen a concomitant boom in fish marketing in nearby auction houses. It present ethnographic data on seven families whose fishermen-husbands virtually abandoned fishing and assumed household management while their wives took on work as full-time fishmongers. The fishermen coped with the loss of economic clout by asserting masculine power, which resulted in spousal tensions, restrictions on their wives' mobility and social lives, and incidents of domestic violence."